The SOS system: A complex and tightly regulated response to DNA damage - Maslowska, Katarzyna H.; Makiela‐Dzbenska, Karolina; Fijalkowska, Iwona J. (Environmental and molecular mutagenesis, 2019)
Genomes of all living organisms are constantly threatened by endogenous and exogenous agents that challenge the chemical integrity of DNA. Most bacteria have evolved a coordinated response to DNA damage. In Escherichia coli, this inducible system is termed the SOS response. The SOS global regulatory network consists of multiple factors promoting the integrity of DNA as well as error‐prone factors allowing for survival and continuous replication upon extensive DNA damage at the cost of elevated mutagenesis. Due to its mutagenic potential, the SOS response is subject to elaborate regulatory control involving not only transcriptional derepression, but also post‐translational activation, and inhibition. This review summarizes current knowledge about the molecular mechanism of the SOS response induction and progression and its consequences for genome stability. Environ. Mol. Mutagen. 60:368–384, 2019. © 2018 The Authors. Environmental and Molecular Mutagenesis published by Wiley Periodicals, Inc. on behalf of Environmental Mutagen Society.